The Impact of Ethics on Job criminalization - Arbabi, Narjes (2021)
The criminalization of some jobs can be traced in the law system of all countries. The criteria for this criminalization vary according to the legal system of each country. In Iran, job criminalization is based on the approach of Imami jurisprudence, which is a text-oriented and sometimes intellect-oriented paradigm. Therefore, jurisprudence determines whether a job is criminal or not. Along with theology and ethics, the science of jurisprudence constitutes the three scientific pillars of Islam. The relationship between these three is one of the fundamental discussions that have great impacts on the attitude of scholars of jurisprudence in dealing with issues. Among these, the relationship between ethics and jurisprudence is very important because these two are formed on the basis of instructions and warnings and it has caused a disagreement among Islamic scholars about their relationship. Some deny their relationship, some believe that ethics requires jurisprudence, and some consider jurisprudence to require ethical supervision. These variations have led to differences in their perceptions of issues. Of course, looking at the meaning of ethics and jurisprudence, it is clear that the two are in close contact with each other, and since human behavior must be accepted by God in order to lead to human happiness, ethics acts as an observer of jurisprudence. This effect is sometimes based on the imaginary and affirmative principles of jurisprudence, and sometimes on the methods of jurisprudence. These effects can be observed in the difference between a job criminalization, which is mentioned in this article.